ISGEN: A Byte Stream Instruction Set Generator - Arci, F. D. L.; Bennett, J. P. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1992: Anais do IV Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1992.22718, 1992)
Various methodologies have been devised for the design of byte stream instruction sets (Tan78, SS82). The second author has proposed on approach that is largely automatic(Ben88). A set of instructions is derived that is optimal according to some criterion, such as the size of compiled code. The choice of instructions is driven by statistical analysis of a large amount of high level language code intended for the instruction set under design. We describe a computer program which will produce such on instruction set. The system has been successfully used to produce bytestream instruction sets to support BCPL (RWS80). Poly(Mat85) and EuLisp (PN+90). We present quantitative results showing the success of these designs. Byte stream instruction sets are now largely restricted to interpretive intermediate codes, with the majority of instruction sets being RISC, or derived designs. We outline current work to produce ISGEN-GA which will generalise the methodology, so that RISC type instruction sets can be produced automatically.